Fabrication and Operation of Flow-Through Tubular SOFCs for Electric Power and Synthesis Gas Cogeneration from Methane - Shi, Huangang; Su, Chao; Yang, Guangming; Ran, Ran; Hao, Yong; Tade, Moses; Shao, Zongping (John Wiley & Sons, Inc., 2014)
Flow-through type tubular solid oxide fuel cells were successfully fabricated and operated with a single-chamber configuration for realizing the simultaneous generation of electric power and synthesis gas from methane by integrating a downstream catalyst into the fuel cell reactor. A new operation mode, which completely eliminated the gas diffusion between cathode side and anode side, is proposed. The cell showed high open-circuit voltages of 1.02–1.08 V at the furnace temperature range of 650–800°C when operating on CH4-O2 gas mixture at a molar ratio of 2:1. A peak power density of approximately 300 mW cm-2 and a maximum power output of 1.5 W were achieved for a single cell with an effective cathode geometric surface area of 5.4 cm2 at the furnace temperature of 750°C. The in-situ initialization of the cell using CH4-O2 gas mixture was also realized via applying an effective catalyst into the tubular cell.